Związki Fizyczne Materiału Sprężystego Odcinkami Liniowego - Szweycer, A.; Wesołowski, Z. (Engineering Transactions, 1972)
The six-dimensional space of stresses is divided into a certain number of disjunct regions. Each of the regions is characterized by a different linear stress-strain relation. The continuity of these relations requires the boundaries of the regions to be five-dimensional hyperplanes. Equations of these hyperplanes are found as a]so the admissible jumps of elastic constants in the case of a general symmetry and for an isotropic body. It is shown that no three region can be conterminous with each other. The resulting equations may be derived by means of a mirror image from the equations which have been previously published by one of the authors.